(untitled) (Revista Tempo e Argumento, 2016)
Abstract In this study, we present Club Fotográfico de México, an institution that focuses on amateur photography in Mexico city, in the first years of its operation, in the 1950s. We understand that photo clubs are a path to be explored by photography history, from the moment they are presented as social spaces in which several issues that involve the practice and theory of photographic image can be observed, from the photograph statute to the country’s propagandistic image. In this sense, Club Fotográfico de México had a central role in the construction of a ‘folklorized’ image of the country and its popular culture and landscapes, thus contributing to consolidate a pro-government identity model, mainly through its guidelines for the creation of photographic image, leading amateur photographers from their choices of topics, going through the techniques and aesthetics that may be used to photograph the country, its landscapes, its culture, and its people. Keywords: Amateur photography; Photo clubs; Mexico; Mexicanidad. Original title: A fotografia amadora no México: Club Fotográfico de México e a presença da folclorização na construção da identidade nacional mexicana - 1950.